“TIVE A OPORTUNIDADE DE VIVER PORQUE CORTEI A SINA”: TRAJETÓRIAS E MEMÓRIAS DE MORADORES DO BAIRRO MERCADINHO NA CIDADE DE IMPERATRIZ-MA - OLIVEIRA, Margarida da Conceição (2024)
The central proposal of this master’s thesis is to think about the social weaves that take place in the city from the collective memory of the residents of the Mercadinho neighborhood, and is of relevance to scientific research on regional theme because it reveals how the emergence of a neighborhood can influence the dynamics of a city, as well as affect individuals who desire improvement of life from the moment they arrive in this city. Beginning with regional authors to understand the emergence and development of the Mercadinho neighborhood in the city of Imperatriz-MA, such as Franklin (2005), Sanches (2002), Da Conceição (2016) and Rodrigues (2012), who focused on themes that intersect with the history of the neighborhood. Later, I carry out an analysis of the studies of memory, starting from some works that work on the concept: Remembrance and Memory, by Bosi (1987), the Invention of the Daily Routine, by Certeau (1980); Collective Memory of Halbwachs (1990), Memory and Forgetfulness, by Pollak (1989), to observe the methodologies used in the field of research and insertion of interlocutors. My field research focuses on methodologies such as informal conversations, analysis of narratives and memories, audiovisual records as a link between me and the interlocutors for the next meeting. The places occupied by residents in the neighborhood of Mercadinho have similar aspects about their place of origin, thus creating an environment that recalls this space. It is also point of attention of this research the reasons why they led to move to the city of Imperatriz and settle in the neighborhood, in search of a new space to survive, fleeing from hunger, agrarian violence and lack of perspective. Most of these people today are in the age range between 60 and 80 years, so I am working with interlocutoras/es elderly/ them, that is, crossed by memories sometimes traumatic, sometimes airosas about their displacement processes to the neighborhood. In the meantime, the research revealed that residents of the neighborhood Mercadinho weave very deep relationships with the space of the neighborhood and also with the neighborhood, concomitantly. They constantly remember their places of origin, according to the experience of these interlocutors who bring familiarities and make them remain until today. For example, they highlight that characteristics such as planting in the background of the backyards and the relationships of neighborhoods that generate a community environment, thus making these memories of their arrivals, Movements, establishments and stays are latent in their stories and memories.